Meminimalkan Kesulitan Menyelesaikan Soal-Soal Matematika Melalui Pembelajaran Problem Based Learning Pada Siswa Kelas Viii SMP Negeri 1 Teras Tahun 2014/2015 - Utami, Rita Sari Sekar, Prof. Dr. Sutama, M.Pd (2015)
The purpose of research to describe the difficulty of students in solving mathematical problems can be minimized through the strategy of Problem Based Learning on students of class VIII F SMP Negeri 1 Teras year 2014/2015. The approach this research is qualitative to the design of classroom action research. Techniques of data collection, observation, testing, field notes, and documentation. The data obtained in the form of scores in the first cycle and cycle II. Data analysis techniques with methods of flow and the comparative method. The results showed the difficulties of students in solving mathematical problems can be minimized seen from: 1) students' difficulties in transferring knowledge before action 46.88%, 15.63% the first cycle, and the second cycle of 6.25%, 2) students' difficulties in visual perception before actions 65.63%, the first cycle of 50%, and the cycle II 6.25%, 3) students' difficulties in calculating the before actions 93.75%, 46.88% the first cycle, and the cycle II 21.88%.